The Execution of Personal Guarantees (Borgtocht) on Working Capital Loans in Bankruptcy Cases: a Study of Indonesian Supreme Court Decision No. 141/Pdt.Sus- PKPU/2020/PN.Niaga.Jkt.Pst - Indri Syahfitri; Iwan Erar Joesoef; Muthia Sakti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research analyzes the impact of Indonesian Supreme Court Decision No. 141/Pdt.Sus- PKPU/2020 on the execution of personal guarantees (borgtocht) in bankruptcy proceedings. This decision is significant as it has the potential to alter the practice of borgtocht execution and affect legal certainty for both creditors and debtors. The research employs a normative method with a statutory approach and case studies. Legal sources include legislation, legal literature, and relevant court decisions. The findings indicate that the Supreme Court decision provides clarity regarding the position of borgtocht in bankruptcy, yet also raises some legal uncertainties. This research offers recommendations for legal improvements regarding borgtocht execution to ensure legal certainty and fairness for all parties involved..